2008
DOI: 10.17221/2362-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bio-rational insecticides on some biological aspects of the Egyptian cotton leafworm Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae)

Abstract: The bio-rational insecticides Dipel 2x, BioFly, Agrin, BioGuard, Spinosad, Neemix, Mectin and Match were tested for their effect on 1<sup>st</sup>, 3<sup>rd</sup> and 5<sup>th</sup> instar larvae and egg masses (24, 48 and 72 h old) of the Egyptian cotton leafworm <i>Spodoptera littoralis</i> under laboratory conditions. The doses used were the recommended dose, half of the recommended dose and quarter of the recommended dose. All insecticides caused higher morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Lufenuron (Match ® ) showed very low toxicity against the first instar larvae of TLM, but no toxicity was observed against fourth instar larvae with subsequent lower reduction in TLM infestation under field conditions. These results are in disagreement with those reported by Osman and Mahmoud (2008) who demonstrated that Match ® gave 100% mortality of 5 th instar larvae of S. littoralis.…”
Section: Discussioncontrasting
confidence: 99%
“…Lufenuron (Match ® ) showed very low toxicity against the first instar larvae of TLM, but no toxicity was observed against fourth instar larvae with subsequent lower reduction in TLM infestation under field conditions. These results are in disagreement with those reported by Osman and Mahmoud (2008) who demonstrated that Match ® gave 100% mortality of 5 th instar larvae of S. littoralis.…”
Section: Discussioncontrasting
confidence: 99%
“…Also the field experiment showed high mortality 91.4% after 2 days then reduced gradually to reach 83.1% after 8 days. Osman and Mahmoud (2008). Semi field studies: Data in Tables (2&3) showed the efficiency of recommended concentrations of Spinetoram and Dipel 2X against 2 nd and 4 th larval instars of S. littoralis under semi field condition.…”
Section: Filed Studiesmentioning
confidence: 99%
“…In this opinion, Tanani et al, (2021) reported that the reduction of protein content in larvae and pupae of Galleria mellonella after larval treatment with the tested arthropod venoms, can be interpreted in the light of some conceivable suggestions: "(1) the proteins might be due to their binding with the tested arthropod venoms and therefore might reflect the depressed activity of the detoxifying enzymes. (2) that the protein plays a major role in synthesis of the microsomal detoxifying enzymes against toxicants (foreign compounds) entering into the insect body (Hassan, 2002). (3).…”
Section: Biochemical Compositionmentioning
confidence: 99%